Peningkatan Hasil Belajar PPKn melalui Model Time Token pada Peserta Didik Kelas V SD GMIT Ende 4 - Maria Kewa; Agustinus F. Paskalino Dadi; Adi Neneng Abdullah (Program Studi PGSD Universitas Flores, 2020)
This research was motivated by the reality in 5th grade of SD Ende 4 GMIT which includes: 1) the low learning outcomes of PPKn caused by learning processes was not interesting, studentwere not active, and unseriousness students in learning; 2) learning methods that tend to be teacher-centered so that students are less active in learning. The purpose of this study is to: 1) describe the application of the Time Token Learning Model in the learning implementation plan and the mechanism of its implementation in learning the PPKn at 5th grade of SD GMIT Ende 4; 2) describe the learning outcomes of students in learning PPKn in 5th grade of SD Ende 4 GMIT after applying the Time Token Learning Model. This method of research is a classroom action research study consisting of 2 cycles, where each cycle applies Action Research Design by Kurt Lewin which includes the stages of planning, implementing actions, observing and reflecting. The method of data collection methods are tests, observations, interviews and document studies. The results of this research is Time Token Model can improve the learning outcomes of PPKn on 5th grade students of SD GMIT Ende 4. This is evidenced by the average value of learning outcomes and the percentage of students completeness classical after the Time Token Model is applied. At the time of the pretest, the average value of PPKn learning outcomes was 53.57, with a classical completeness percentage is 21.43%. This result has increased in first cycle with average value is 69.64 and the percentage of classical completeness is 35.71%. In second cycle, learning outcomes average value has increased to 99, 28, with percentage of classical completeness is 100%.